Adsorption Equilibria of Natural Gas Components on Activated Carbon: Pure and Mixed Gas Isotherms - R.E. Bazan; M. Bastos-Neto; R. Staudt; H. Papp; D.C.S. Azevedo; C.L. Cavalcante (Adsorption Science & Technology, 2008)
A typical Natural Gas (NG) composition in South America contains ca. 86% methane, 10% ethane, 1.5% carbon dioxide, 1% nitrogen and other heavier hydrocarbons. The composition plays an important role in studies of NG storage systems since heavier alkanes may accumulate in the adsorbent bed, saturate it in long-term use and affect the storage capacity. In this study, measurements of experimental data for the adsorption equilibria of binary mixtures of CH 4 with C 2 H 6 , CO 2 , C 3 H 8 and N 2 — as obtained in a volumetric/chromatographic set-up — are presented and compared with mathematical models for multi-component adsorption based on pure component adsorption data. Experimental results were compared with predictions from the Extended Langmuir (EL) model and the Ideal Adsorbed Solution Theory (IAST) model. The IAST model was capable of providing a more accurate fit to most of the obtained data, other than those measured for the least adsorbed gases (CH 4 /N 2 ).